Meningkatkan Hasil Belajar Matematika Materi Penyajian Data Menggunakan Model Problem Based Learning (PBL) Pada Siswa Kelas V Di UPTD SDN 1 Kait-Kait Kabupaten Tanah Laut - Nor Latifah; Sunarno (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
The problem in this study is that learning is one-way, there is no learning that can stimulate students to improve problem-solving skills, and learning is still not varied. The purpose of this research is to describe the activities of educators and students and to increase learning outcomes. This study uses a qualitative approach with the type of Classroom Action Research (CAR). The type of data used is qualitative data in the form of observing the activities of educators and students during learning activities as well as quantitative data namely learning outcomes in the cognitive, affective and psychomotor domains. These results show that the activity of educators in cycle I reached 17 "very good" criteria and increased in cycle II to 19 with "very good" criteria. Student activity in cycle I reached 66.67% with the "active" criteria and increased in cycle II to 94.44% with the "very active" criteria. Learning outcomes in the cognitive and affective domains in cycle I reached 61.11%, psychomotor reached 66.67%, and increased in cycle II to 100%. It was concluded that there was an increase in educator activity, student activity and learning outcomes using the Problem Based Learning (PBL) model.